2017
DOI: 10.1111/1440-1681.12860
|View full text |Cite
|
Sign up to set email alerts
|

Opioid receptors mediate inotropic and depressor effects of apelin in rats with 2K1C‐induced chronic renovascular hypertension

Abstract: Apelin receptors (APJ) cross-talk with other G-protein-coupled receptors. However, the role of APJ interaction with opioid receptors (OPR) on the cardiovascular effects of apelin in hypertension is not clear. Renovascular hypertension was induced by placing a Plexiglas clip on the left kidney of rats. After 16 weeks, F13A (an APJ antagonist), naloxone (a general OPR inhibitor), and nor-binaltorphimine dihydrochloride (nor-BNI; a selective inhibitor of KOR) were given prior to injections of apelin at doses of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…This was also associated with antagonizing the apelin‐induced reduction in AT1R expression (Figure ). Similarly the results of our previous study have shown that kappa opioid receptors mediate and potentiate the impacts of apelin on increasing cardiac contractility through its receptors . The findings of the present study also show that even endogenous apelin has an important effect on conserving mechanical function of the myocardium, as pretreatment with F13A had significantly impaired contractility indices of the heart such as LVDP and + dp/dt max (see Table ).…”
Section: Discussionsupporting
confidence: 90%
“…This was also associated with antagonizing the apelin‐induced reduction in AT1R expression (Figure ). Similarly the results of our previous study have shown that kappa opioid receptors mediate and potentiate the impacts of apelin on increasing cardiac contractility through its receptors . The findings of the present study also show that even endogenous apelin has an important effect on conserving mechanical function of the myocardium, as pretreatment with F13A had significantly impaired contractility indices of the heart such as LVDP and + dp/dt max (see Table ).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in other receptor systems have shown compensatory changes in gene expression following injection of gene-specific lenti- or adenoviral constructs ( Chen et al, 2006 ; Blume et al, 2013 ). APJ interacts with other receptors to regulate the cardiovascular system ( Gurzu et al, 2006 ; Rostamzadeh et al, 2017 , 2018 ), and forms heterodimers in vitro with other GPCRs e.g., the angiotensin II receptor ( Chun et al, 2008 ), the kappa opioid receptor ( Li et al, 2012 ), the neurotensin 1 receptor ( Bai et al, 2014a ) and the bradykinin 1 receptor ( Bai et al, 2014b ), to selectively regulate cellular responses mediated by apelin. It is tempting to speculate that the V1a vasopressin receptor (V1aR), a key modulator of cardiovascular regulation ( Japundžić-Žigon, 2013 ), might be capable of forming heterodimers with APJ.…”
Section: Discussionmentioning
confidence: 99%
“…F13A demonstrated dose-dependent inhibition of apelin-induced hypotensive effects, with no effect on Ang II-induced hypertensive effects, indicating selectivity of F13A toward apelin-induced responses (Lee, et al, 2005). F13A also attenuated apelin-induced depressor responses during renovascular hypertension (Rostamzadeh, et al, 2018) and, in isolated rat cerebral arteries, F13A abolished the inhibitory effects of apelin on BK Ca channel function and NO-induced relaxation (Mughal, et al, 2018). Moreover, pressor responses to centrally administered apelin in both normotensive and hypertensive rats are significantly attenuated by pre-treatment with F13A (Zhang, et al, 2014a; Griffiths, et al, 2017).…”
Section: Apelin Mimetics and Inhibitorsmentioning
confidence: 99%
“…In animal models of pulmonary hypertension and diabetes, apelin treatment lowered mean arterial pressure and reduced the levels of vasoconstrictor mediators such as angiotensin-II and endothelin-1 (Akcilar, et al, 2013; Falcao-Pires, et al, 2009). Similarly, intravenous bolus administration of apelin caused a significant reduction in mean pulmonary arterial pressure during acute pulmonary embolism (Feng, et al, 2010), and apelin signaling via APJ – KOR heterodimers caused a depressor response during renovascular hypertension (Yeganeh-Hajahmadi, et al, 2017; Rostamzadeh, et al, 2018). Moreover, by increasing eNOS phosphorylation, apelin reversed the impaired relaxation response to acetylcholine and abrogated abnormal Ang II-induced contractile tone in intrarenal arteries from diabetic mice (Zhong, et al, 2007a).…”
Section: Vascular Effects Of Apelinmentioning
confidence: 99%